Thermal analysis of a high-power glow discharge in flowing atmospheric air by combining Rayleigh scattering thermometry and numerical simulation. (12th December 2019) - Kong, Chengdong; Li, Zhongshan; Aldén, Marcus; Ehn, Andreas
Abstract: The thermal state of a glow discharge with intermediate current in flowing atmospheric air is investigated by a combination of Rayleigh scattering thermometry imaging and numerical simulation. Results from the simulation indicate that during the initial breakdown the local translational temperature can reach a huge value (e.g. 6000 K) but decreases quickly due to strong heat transfer to the surrounding cold air. In the gliding stage, the translational temperature of plasma is balanced by the input power density and the heat dissipation rate. As the gas flow rate is increased, the translational temperature in the glow plasma column diminishes. The flow affects the thermal state of plasma from two aspects. First, it promotes elongation of the plasma column to decrease the input power density. Second, the flow enhances local heat dissipation. As a result, the translational temperature is lowered due to flow. Using a two-temperature model, which considers the translational temperature, the vibrational temperature and their transitions, the non-thermal state of plasma is further analyzed. The gas flow is found to reduce the translational temperature and the vibrational–translational relaxation rate, and thus prevent thermalization of the plasma column.